MORPHOLOGICAL CHARACTERIZATION OF PLANTAIN SQUIRREL (Callosciurus notatus) SPERM - Muhimatul Umami (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2022)
The plantain squirrel (Callosciurus notatus) is a rodent of the family Sciuridae. The population of plantain squirrels in Indonesia has decreased every year. The 2019 Checklist of the Mammals of Indonesia reports that the plantain squirrel is in a low concentration status; thus, accelerated efforts in wildlife conservation, including integrating technology with conservation efforts, are necessary. This study aims to determine the morphological characteristic of the plantain squirrel spermatozoa. This research consisted of several stages: anesthesia of animal samples, surgery, a maceration method, observation of the spermatozoa morphology using William's staining, and morphometry of sperm using ImageJ 1.46r software. The results show that the plantain squirrel sperm has a slightly flat head shape, falciform with one apical hook, and a not too long tail. The average sperm head length is 1.87 ± 0.30 µm, the average sperm tail length is 5.48 ± 0.95 µm.